The effect of body mass index on the development of acute kidney injury and mortality in intensive care unit: is obesity paradox valid? - (:unkn) unknown (TAYLOR & FRANCIS LTD, 2021)
Background The conflicting results of studies on intensive care unit (ICU) mortality of obese patients and obese patients with acute kidney injury (AKI) reveal a paradox within a paradox. The aim of this study was to determine the effects of body mass index and obesity on AKI development and ICU mortality. Methods The 4,459 patients treated between January 2015 and December 2019 in the ICU at a Tertiary Care Center in Turkey were analyzed retrospectively. Results AKI developed more in obese patients with 69.8% (620). AKI development rates were similar in normal-weight (65.1%; 1172) and overweight patients (64.9%; 1149). The development of AKI in patients who presented with cerebrovascular diseases was higher in obese patients (81; 76.4%) than in normal-weight (158; 62.7%) and overweight (174; 60.8%) patients (p < 0.05). The risk of developing AKI was approximately 1.4 times (CI 95% = 1.177-1.662) higher in obese patients than in normal-weight patients. Dialysis was used more frequently in obese patients (24.3%, p < 0.001), who stayed longer in the ICU (p < 0.05). It was determined that the development of AKI in normal-weight and overweight patients increased mortality (p < 0.001) and that there was not a difference in mortality rates between obese patients with and without AKI. Conclusion The risk of AKI development was higher in obese patients but not in those who were in serious conditions. Another paradox was that the development of AKI was associated with a higher mortality rate in normal-weight and overweight patients, but not in obese patients. Cerebrovascular diseases as a cause of admission pose additional risks for AKI.
Keywords: Acute kidney injury; body mass index; obesity; mortality; intensive care unit; obesity paradox; mechanical ventilation